2020
DOI: 10.3233/prm-190667
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic bowel treatments and continence outcomes in children and adults with myelomeningocele

Abstract: PURPOSE: Neurogenic bowel dysfunction (NBD) is a common comorbidity of myelomeningocele (MMC), the most common and severe form of spina bifida. The National Spina Bifida Patient Registry (NSBPR) is a research collaboration between the CDC and Spina Bifida Clinics. Fecal continence (continence) outcomes for common treatment modalities for NBD have not been described in a large sample of individuals with MMC. NSBPR patients with MMC and NBD were studied to determine variation in continence status and their abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Nevertheless, similar to the other outcomes in some instances where drastically superior results were achieved such as a rate of close to 20% incontinence in patients reported by Behbahani et al from Lurie Children’s Hospital [ 23 ]. As outlined in our results and reported previously, there is a correlation between the urinary and bowel continence and school attendance [ 31 ]. This finding may be emphasized in settings with limited special education facilities, like the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, similar to the other outcomes in some instances where drastically superior results were achieved such as a rate of close to 20% incontinence in patients reported by Behbahani et al from Lurie Children’s Hospital [ 23 ]. As outlined in our results and reported previously, there is a correlation between the urinary and bowel continence and school attendance [ 31 ]. This finding may be emphasized in settings with limited special education facilities, like the present study.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the increased time required for bowel emptying with ACE flushes, and insufficient mobility of some patients with spinal lesions to administer rectal enemas or TAIs, fecal diversion might be the optimal treatment option taking much less time [ 22 ]. Kelly et al reported the highest independence rates achieved with fecal diversion (63%), followed by ACE flushes (49%), rectal enemas (22%), and TAIs (13%) as demonstrated in Figure 2 [ 35 ].…”
Section: Factors Affecting Continence and Treatmentmentioning
confidence: 99%
“…Various studies show that surgical treatment of NBD can be effective in supporting an enhanced QoL if properly indicated and with patients carefully selected 63 . However, a recent study found that roughly 40% of paediatric and adult patients with NBD attributable to myelomeningocele require surgery (due to failure of medical treatment) in order to attain faecal control 101 . Most reports on surgical treatment of NBD deal with adult patients and very little has been published on children and adolescents on this topic.…”
Section: -Lmentioning
confidence: 99%